(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the impact of Electronic Smoking Devices (ESDs) on public health, exploring various medical specialties (pulmonology, endocrinology, oncology, psychiatry, cardiology, and vascular medicine) and their related consequences. Methodology: This article is an integrative literature review following the steps proposed by Mendes, Silveira, and Galvão (2008). The research was conducted in digital databases, PubMed and SciELO, covering the years 2021 to 2024, analyzing 19 relevant studies. Results: The results showed that ESDs are associated with several negative impacts on public health across different medical specialties. The most frequently observed consequences are related to the respiratory system, such as respiratory difficulties and lung injuries (EVALI). Conclusion: Although initially perceived as safer alternatives compared to traditional cigarettes, electronic smoking devices pose significant risks. Findings on their impacts highlight the need for strict public policies and awareness campaigns to minimize their use and protect public health.